An interdisciplinary literature review of floating solar power plants - Wei, Yujia; Khojasteh, Danial; Windt, Christian; Huang, Luofeng (Elsevier, 2025)
Floating photovoltaic is predicted to be the most ubiquitous energy technology in the future, with global installations projected to reach 10 GW by 2030, potentially generating 13.5 TWh of clean electricity annually. The extrapolation of solar power plants from land-based to water-based requires interdisciplinary expertise from fields such as energy systems, hydrodynamics, structures, environments, and electrical engineering. To bridge the disciplines, the present review analyses existing floating solar related publications comprehensively. Initially, a comprehensive literature scan of over 900 publications is presented, selectively leading to approximately 400 papers included. Subsequently, three review sectors are presented: design, modelling, and environmental effects. These cover various structural components, system-air-water interactions, their modelling approaches, power output prediction, and potential impacts on the surrounding environment including vegetation and animals. Key findings suggest the potential for enhancing energy efficiency through water-based cooling techniques, innovative modularised designs to support upscaling, positive environmental impacts including artificial habitats, and the utilisation of advanced marine structure designs such as a breakwater to protect the solar systems from ocean wave loads. In addition, the levelised cost of electricity of various floating solar studies are presented, including both theoretical and practical projects. The levelised cost of electricity has been decreasing, to a level of 0.05–0.07 USD/kWh, making FPV increasingly competitive as a clean and affordable energy choice. Overall, this review aims to facillitate interdisciplinary research and projects on the booming floating photovoltaic industry.
Keywords: Energy; 40 Engineering; Renewable energy; Floating photovoltaic; Design criteria; Computational modelling; Environment effects